Methodological basis for improving accounting of fixed assets in budgetary organizations - Jumaeva Gulrukh Jurakulovna; Bovoboev Saidmurod Norkuzi oglu, (THE INNOVATION ECONOMY, 2026)
The article examines methodological foundations for improving fixed asset accounting in budget organizations. It identifies weaknesses in the current system and proposes an improved model that systematizes asset valuation, depreciation, and revaluation, ensuring accurate inventory reporting and enhancing the quality of financial statements. The study also highlights the importance of digital accounting systems and strengthened internal controls. The proposed approach helps improve asset utilization efficiency, ensures reliable and timely accounting, and reinforces financial discipline within budget organizations